Nerve Growth Factor Serum Levels Are Associated With Regional Gray Matter Volume Differences in Schizophrenia Patients - Neugebauer, Kristina; Hammans, Christine; Wensing, Tobias; Kumar, Vinod; Grodd, Wolfgang; Mevissen, Lea; Sternkopf, Melanie A.; Novakovic, Ana; Abel, Ted; Habel, Ute; Nickl-Jockschat, Thomas (Frontiers in Psychiatry, 2019)
Numerous neuroimaging studies have revealed structural brain abnormalities in schizophrenia patients. There is emerging evidence that dysfunctional nerve growth factor (NGF) signaling may contribute to structural brain alterations found in these patients. In this pilot study, we investigated whether there was a correlation between NGF serum levels and gray matter volume (GMV) in schizophrenia patients. Further, we investigated whether there was an overlap between the correlative findings and cross-sectional GMV differences between schizophrenia patients and healthy controls. Serum NGF was significantly correlated to GMV in the left prefrontal lobe, the left midcingulate cortex and the brainstem in schizophrenia patients. However, we did not find any correlations of NGF serum levels with GMV in healthy controls. Schizophrenia patients showed smaller GMV than healthy controls in brain regions located in the bilateral limbic system, bilateral parietal lobe, bilateral insula, bilateral primary auditory cortex, left frontal lobe and bilateral occipital regions. In a conjunction analysis, GMV in the left midcingulate cortex (MCC) appears negatively correlated to NGF serum levels in the group of schizophrenia patients and also to be reduced compared to healthy controls. These results suggest an increased vulnerability of schizophrenia patients to changes in NGF levels compared to healthy controls and support a role for NGF signaling in the pathophysiology of schizophrenia.